ATTITUDES OF PLWHA AND OTHER SELECTED COMMUNITIES IN TSABONG TOWARDS OPERATIONALISING BIOMEDICAL AND TRADITIONAL THERAPIES IN TANDEM TO FACE THE AIDS EPIDEMIC - Kang’ethe, Simon (Social Work/Maatskaplike Werk, 2012)
Though the broad research study from which this article is derived was designed to assess the levels of stigma and discrimination in Tsabong District, the aim and objective of this article is to assess the attitudes of Tsabong people living with HIV/AIDS, along with those of a few Tsabong care service providers and a few members of civil society to the challenges and gaps inherent in the work of biomedical and traditional healers in HIV/AIDS service delivery. It also investigates the possibility of collaboration between the two systems.